Abdullah Saeed’s Contextual Approach to The Qur’an: Interpretation of Q. 24: 31 - Dzikrillah Alfani, Ilzam Hubby; Mukhsin Mukhsin (STAIN Sultan Abdurrahman Kepulauan Riau, 2024)
The study of Q. 24: 31 is not new in the world of Quranic exegesis, as various methods and approaches in the field have been used to explore the main message of Q. 24: 31. Explicitly, Q. 24: 31 commands the preservation of dignity by covering one’s body (aurat). However, the core message has undergone distortion due to current phenomena. In both the real and virtual worlds, many claim to exhibit Islamic character, yet their behavior contradicts the ethical and religious norms. This can be seen in trends such as jilboobs, turbans, Yakult bottles, and others. Building upon these phenomena, this study aims to reassess the interpretation of Q. 24: 31 and its contextual relevance. This qualitative research relies on a literature review as its primary method of analysis. The data is analyzed descriptively using Abdullah Saeed's contextual approach. The study concludes that historically, women of the past did not wear the khimar properly, merely draping it over their heads, leaving parts of their bodies exposed. In response, Q. 24: 31 provides specific guidance on the norms and ethics that Muslim women should follow, including wearing a khimar that fully covers the head and chest. Q. 24: 31 is universal, as evidenced by its repetition in other verses, indicating that its values are constant and comprehensive. The contextualization of Q. 24: 31 for today serves as a guide not only for covering the body but also for adhering to the norms and ethics of Islam. Covering the body should be accompanied by maintaining a woman’s dignity and honor, which is an integral part of observing modesty.